Genome-Wide Association Study Identifies New Candidate Markers for Somatic Cells Score in a Local Dairy Sheep - Sutera, Anna Maria; Moscarelli, Angelo; Mastrangelo, Salvatore; Sardina, Maria Teresa; Di Gerlando, Rosalia; Portolano, Baldassare; Tolone, Marco (Frontiers in Genetics, 2021)
In the Mediterranean basin countries, the dairy sheep production is usually based on local breeds, which are very well adapted to their production systems and environments and can indeed guarantee income, employment and economic viability in areas where production alternatives are scarce or non-existent. Mastitis is still one of the greatest problems affecting commercial milk production. However genetic evaluation of mastitis is particularly difficult because of its low heritability and the categorical nature of the trait. The aim of this study was to identify genomic regions putatively associated with somatic cells count (SCC) in the local economically important Valle del Belice sheep breed using of deregressed breeding values (DEBV) as response variables. All the samples were genotyped using the Illumina OvineSNP50K BeadChip. Genome-wide association analysis was carried out based on regression of DEBV. A total of 8 markers were found to be significantly associated with log-transformed SCC. Several candidate genes associated with SCC were identified related to immunity system and udder conformation. The results can help improving the competitiveness of the local Valle del Belìce breed. Anyway, further studies considering a higher sample size or independent population will be needed to confirm our results.